Monthly distribution of zooplankton in Kapikaya Reservoir, Turkey - Bulut, Hilal; Saler, Serap (Maejo Univ, 2020)
The zooplankton of Kapikaya Reservoir were investigated monthly. A total of 38 species were identified, i.e. 30 Rotifera (79%), 5 Cladocera (13%) and 3 Copepoda (8%) species. Samples were taken monthly from two stations from Kapikaya Reservoir between March 2013 and February 2014. Water temperature, pH and dissolved oxygen were determined in situ. Rotifera was the most dominant among the zooplankton groups. The rotifers Keratella cochlearis and Polyarthra dolichoptera were observed in all months. The cladoceran Bosmina longirostris and copepod Cyclops vicinus were the dominant species of their groups. In the present study the Shannon Wiener index showed that species richness was highest at the 1st station in March (H' = 2.72) and lowest at the 2nd station in January (H' = 0.69). According to the Margalef index for this reservoir, the highest value in March at the 1st station was 1.81, and the lowest value in January at the 2nd station was 0.14.
Keywords: Kapikaya Reservoir; Cladocera; Copepoda; Rotifera; Zooplankton; Turkey